PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SMARTPHONE MEREK SAMSUNG PADA PEGAWAI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA DEPOK - Veni Apriani; Antoni Ludfi Arifin (Jurnal Inovasi Penelitian, 2020)
The research purpose is to analyze the Effect of Brand Image and Product Quality on Buying Interest of Samsung Brand Smart Phone Product in the Employee of Environment and Sanitary Office of Depok City partially and simultaneously. The analysis technique uses double linear regression analysis. The data analysis uses IBM SPSS Statistics program 24 version. The research population is Population in this research is the Employee of Environment and Sanitary Office of Depok City of 89 persons, by using Census obtained 89 samples. The research result: (1) There is positive and significant effect of Brand Image on the Buying Interest of Samsung Brand Smart Phone Product in the Employee of Environment and Sanitary Office of Depok City stated accepted with the size of correlation effect of 0,758 and the determination effect of 42,8%. (2) there is positive and significant effect of Product Quality on the Buying Interest of Samsung Brand Smart Phone Product in the Employee of Environment and Sanitary Office of Depok City stated accepted with the size of correlation effect of 0,783 and the determination effect of 61,4%. (3) There is positive and significant effect of Brand Image and Product Quality simultaneously on the Buying interest of Samsung Brand Smart Phone Product in the Employee of Environment and Sanitary Office of Depok City stated accepted with the size of correlation effect of 0,831 and the determination effect of 69,1%.